Women and Politics: The privacy without necktie - López-Hermida Russo, Alberto Pedro (2022)
The arrival of Michelle Bachelet at the Chilean government did not simply mean that a South American country had its first female president; it also brought a new way of doing politics and, for the media, a new way of approaching the highest national authority. The TV electoral campaign, as well as the press coverage of her presidential activities, brought the exploration of an almost unknown world in the public sphere: personal life of Bachelet.This paper will analyze the evidence found in her electoral spots and in the media, that will allow tackling the object of study and understand the role of the gender in the degree and nature of exposure of the private lives of politicians.